2021
DOI: 10.1007/s00590-021-02987-1
|View full text |Cite
|
Sign up to set email alerts
|

Anterior deltoid muscle tension quantified with shear wave ultrasound elastography correlates with pain level after reverse shoulder arthroplasty

Abstract: Introduction Reverse shoulder arthroplasty (RSA) leads to medialization and distalization of the centre of rotation of the shoulder joint resulting in lengthening of the deltoid muscle. Shear wave ultrasound elastography (SWE) is a reliable method for quantifying tissue stiffness. The purpose of this study was to analyse if deltoid muscle tension after RSA correlates with the patients’ pain level. We hypothesized that higher deltoid muscle tension would be associated with increased pain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…14,15 Recently, several studies have used SWE to examine the biomechanical properties of the deltoid muscle post reverse shoulder arthroplasty and noted that the stiffness of the deltoid muscle increased post reverse shoulder arthroplasty. [16][17][18] Therefore, when rehabilitating the shoulder post rotator cuff repair, it is important to consider both the rotator cuff and the deltoid muscle.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 Recently, several studies have used SWE to examine the biomechanical properties of the deltoid muscle post reverse shoulder arthroplasty and noted that the stiffness of the deltoid muscle increased post reverse shoulder arthroplasty. [16][17][18] Therefore, when rehabilitating the shoulder post rotator cuff repair, it is important to consider both the rotator cuff and the deltoid muscle.…”
mentioning
confidence: 99%
“…Two biomechanical cadaveric studies demonstrated that in the presence of a rotator cuff tear, significantly increased force in the deltoid muscle was required to achieve stable glenohumeral abduction without excessive superior humeral head translation 14,15 . Recently, several studies have used SWE to examine the biomechanical properties of the deltoid muscle post reverse shoulder arthroplasty and noted that the stiffness of the deltoid muscle increased post reverse shoulder arthroplasty 16–18 . Therefore, when rehabilitating the shoulder post rotator cuff repair, it is important to consider both the rotator cuff and the deltoid muscle.…”
mentioning
confidence: 99%